2013
DOI: 10.7748/nr2013.09.21.1.35.e302
|View full text |Cite
|
Sign up to set email alerts
|

Online social networks for patient involvement and recruitment in clinical research

Abstract: AimsThis paper reviews current literature and discusses the potential for Social Networking websites for engaging patients and the public along with recruitment and retention of participants in clinical research. Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 0 publications
1
38
0
Order By: Relevance
“…For instance, social media seemed to be successful at recruiting hard-to-reach populations [16,17,28,31,32,36] and individuals with specific conditions or disorders [14,16,17,28,31,32]. This finding was in agreement with the findings of Park and Calamaro [12] and Ryan [13]. This is likely because in such a case it is difficult for any one conventional source to find a sufficient number of individuals, as was noted in the study by Johnson et al [16].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…For instance, social media seemed to be successful at recruiting hard-to-reach populations [16,17,28,31,32,36] and individuals with specific conditions or disorders [14,16,17,28,31,32]. This finding was in agreement with the findings of Park and Calamaro [12] and Ryan [13]. This is likely because in such a case it is difficult for any one conventional source to find a sufficient number of individuals, as was noted in the study by Johnson et al [16].…”
Section: Discussionsupporting
confidence: 85%
“…Literature reviews on the role of social media in recruitment have been done by Park and Calamaro [12] and Ryan [13]. These reviews also identified social media as being effective in recruiting both hard-to-reach populations and adolescents and young adults (AYAs), as well as being cost-effective.…”
Section: Introductionmentioning
confidence: 99%
“…7 In the area of health research, use of Facebook has largely centered on recruitment of adults for cross-sectional surveys. Examples include studies of nutrition education programming with low-income Pennsylvania residents; 8 adult therapy preferences; 9 adult sexual orientation; 10 and birth preferences of pregnant women, with costs of $11.11 per enrollee.…”
Section: Introductionmentioning
confidence: 99%
“…Several recent efforts have successfully used Facebook to recruit young adults including sexual minority young adults, into research studies for a range of health-related topics [16-25]. Several of these studies reported that Facebook was a convenient and cost-efficient strategy for recruiting young adults [17,18,20,22]. …”
Section: Introductionmentioning
confidence: 99%